The Sufi tendencies of Islamic Modernity in the thought of Abd al-Rahman Taha - Soltani, Abdelkader (The International tax journal, 2026)
Abd al-Rahman Taha is regarded as one of the prominent figures of contemporary Arab and Islamic thought. He devoted significant attention to the critical reading of heritage. He also examined and challenged the various approaches that dominated the interpretation of this heritage, regardless of their methods or sources. Within this intellectual project, he called for the establishment of an Arab-Islamic philosophy. This philosophy draws selectively from Western civilization to address internal reform, while preserving the intellectual and scientific foundations of Arab-Islamic heritage. These foundations had once contributed to shaping the course of history in earlier periods. A key feature of Taha’s project is his emphasis on the practical and ethical dimensions of the Islamic alternative to Western modernity. He argued that Western modernity largely neglected this ethical dimension. Many Arab and Islamic readings followed Western methodologies without critical revision or adaptation. This uncritical adoption resulted in a form of intellectual production detached from its cultural roots. It mirrored Western approaches to heritage and led to calls for a complete rupture with Arab-Islamic tradition. In practice, this approach failed to produce tangible progress and remained limited to unproductive discourse.